Zircon geochronology and geochemistry of the Xianghualing A-type granitic rocks: Insights into multi-stage Sn-polymetallic mineralization in South China - Li, H.; Wu, J.; Evans, Noreen; Jiang, W.; Zhou, Z. (Elsevier BV, 2018)
© 2018 Elsevier B.V. Highly evolved Sn-polymetallic mineralization-related granites are intensively developed in the Nanling Range of South China. In this study, two types of granitic rocks (albite granite and greisenized granite) from the Laiziling pluton in the Xianghualing area were studied to elucidate magma evolution and the genesis of mineralization. The A-type Xianghualing granitic rocks are characterized by high SiO2(69.16–85.04%), Rb (759–2110 ppm), Ta (17.2–50.8 ppm), Nd (2.8–82.4 ppm) and87Sr/86Sr (0.907275–4.181262) and low MgO (0.01–0.98%), TiO2(0.01–0.03%), Sr (1.4–70.2 ppm), Ba (1.4–132.5 ppm), Eu (0.03–0.21 ppm) and143Nd/144Nd (0.512283–0.512326). The whole-rock eNd(t) values range from -6.3 to -6.0, with T2DMages of 1426–1454 Ma. The zircon eHf(t) values mostly range from -10 to -5, with dominant TDMCvalues of 1400–1800 Ma. This suggests that the Xianghualing granitic rocks were derived from partial melting of Mesoproterozoic basement rocks in the Cathaysian Block, in a lithospheric extension setting. Zircon U–Pb dating yielded five age clusters: Proterozoic (>900 Ma, n = 9), Silurian (~430 Ma, n = 4), Triassic (~220 Ma, n = 16), Jurassic (~150 Ma, n = 62) and Cretaceous (~80 Ma, n = 28). Zircon internal textures, trace element contents and Hf isotopic compositions indicate that they formed from a range of sources including residual zircons from the magma source region, detrital zircons from local sediments, zircons captured from pre-existing magmatic rocks with obvious mantle signatures, magmatic and fluid-altered zircons, and late stage hydrothermal zircons. This suggests significant fractional crystallization, weak wall-rock assimilation/contamination and intense fluid differentiation/metasomatism during the genesis of the Xianghualing granitic rocks. M-type REE tetrad effects are seen not only in bulk rock compositions, but also in individual zircon grains, indicating that highly fractionated and reduced F-rich fluids played an important role in the formation of Sn-polymetallic mineralization. Guided by the major Mesozoic W–Sn ore-forming events occurring in the Cathaysian Block of South China, a multi-stage genetic model is proposed for the Xianghualing granitic-minerogenic system: initial enrichment of W–Sn in the Triassic (~220 Ma), dominant Sn-polymetallic metal precipitation in the Jurassic (~150 Ma), and superimposed mineralization in the Cretaceous (~80 Ma).